Neurologically presenting Whipple disease: case report and review of the literature. Issue 10 (1st April 2008) - Buckle, M J; Ellis, R W; Bone, M; Lockman, H
Abstract : A previously healthy male with subacute onset right leg weakness was suspected to have an astrocytoma as imaging showed a lesion. Subsequent biopsy showed the presence of foamy macrophages containing periodic acid-Schiff staining granules, suggesting Whipple disease as a possible diagnosis.